Color duplex ultrasonography versus handheld Doppler to plan anterior lateral thigh flaps. Issue 5 (27th March 2017) - Lethaus, Bernd; Loberg, Christina; Kloss‐Brandstätter, Anita; Bartella, Alexander K.; Steiner, Timm; Modabber, Ali; Hölzle, Frank; Teichmann, Jan
Abstract : Background: The anterior lateral thigh flap (ALT) has become increasingly important in reconstructive surgery in the head and neck region. To cope with the problem of anatomical variability in the supplying blood vessels, preoperative evaluation is desirable. Purpose of the study is to compare the most commonly used Doppler devices Handheld Doppler (HD) and Color Doppler Ultrasonography (CDU) for their clinical reliability. Methods: Forty five consecutive head and neck cancer patients (mean age 66.0 ± 11.2 years) were included in the study. They all underwent a reconstruction via ALT flap for a defect in the head and neck area. Study period ranged from May 2014 to August 2015. We preoperatively conducted HD and CDU on the lateral thigh and compared the intraoperative findings by measuring presence of the perforator and distance to the estimated position. Results: There were 95 perforators identified in 45 patients. The sensitivity and positive predictive value (PPV) were calculated as 97.9% and 100% for CDU and 90.5% and 80.4% for HD, respectively. Accuracy was significantly greater with the HD compared to the CDU device ( P < 0.001) and was strongly associated with body mass index (BMI) ( P < 0.001). This effect was stronger in HD than in CDU ( r = 0.800; P < 0.001 versus r = 0.673; P < 0.001). Conclusions: Our results indicate CDU is more precise and reliable than HD with respect to detecting the anatomical position of perforating arteries. © 2017 Wiley Periodicals, Inc. Microsurgery 37:388–393, 2017.